Exploring Humanity in Mega-Mega Arifin C. Noer Through Humanistic Psychology - Rusli Rusli; Ahmad Maskur Subaweh; Muhammad Sholeh (Journal of General Education and Humanities, 2025)
This research aims to reveal the human values in the script of the drama Mega-Mega by Arifin C. Noer through a humanistic psychology approach. The main focus of the research is to answer the question: How do the struggles of the characters in the drama reflect the five levels of human needs according to Abraham Maslow's theory of the hierarchy of needs? These five needs include physiological needs, a sense of security, social relationships, rewards, and self-actualization. The drama Mega-Mega depicts the lives of marginalized groups who struggle to maintain dignity amid social, economic, and political pressures. This study uses a qualitative descriptive method with text Panutysis, identifying the manifestation of Maslow's needs in the behavior and dialogue of the characters. The results show that the conflict in the drama is not only external, but also reflects an existential crisis and the search for meaning in life. Characters like Mae, Koyal, and Retno experience the process of self-actualization through struggle, emotional attachment, and efforts to maintain dignity. Thus, Mega-Mega is not only a social critique, but also a reflective mirror of humanity's struggle in extreme conditions. This study offers a new perspective on the script through the lens of humanistic psychology, which was previously rarely used in the Panutysis of this drama.